Cotransmission of Acetylcholine and GABA - Granger, Adam J (Neuropharmacology, 2015)
Neurons that produce acetylcholine (ACh) are positioned to broadly influence the brain, with axonal arborizations that extend throughout the cerebral cortex, striatum, and hippocampus. While the action of these neurons has typically been attributed entirely to ACh, neurons often release more than one primary neurotransmitter. Here, we review evidence for the cotransmission of the inhibitory neurotransmitter GABA from cholinergic neurons throughout the mammalian central nervous system. Functional cotransmission of ACh and GABA has been reported in the retina and cortex, and anatomical studies suggest that GABA cotransmission is a common feature of nearly all forebrain ACh-producing neurons. Further experiments are necessary to confirm the extent of GABA cotransmission from cholinergic neurons, and the contribution of GABA needs to be considered when studying the functional impact of activity in ACh-producing neurons.